NARIKELA (COCOS NUCIFERA LINN.), A HEIGHTED PALM TREE WITH HIGH MEDICINAL VALUE IN AYURVEDA – A REVIEW - Doshi K. A.; Patel M. H; Patel D. A.; Jani S. S. (International Journal of Applied Ayurved Research, 2015)
Ayurveda delineates the use of Narikela (Cocos nucifera Linn. Arecaceae) in classical texts for the management of different diseased conditions. In this article, an attempt has been made to compile as critically and its information related to Narikela from six samhitas, seven samgraha granthas, nine nighantus and other published texts. It is observed that Fruit, Root, Flower, Fruit milk, Fruit pulp of Narikela are used as an ingredient in 53 formulations, which are effective in more than 25 disease conditions. The main indications include mutraroga (urinary disorders), shula (pain), vajikaran (aphrodisiac), charma roga (diseases of skin ), mutrakruchcha (dysuria), prameha (increased frequency of urine), amlapitta (acidity), raktapitta (bleeding disorder), rasayan (rejuvenating agent) etc. Different parts of Narikela are used in about 15 dosage forms; such as kvatha (decoction), lepa (paste), avaleha (semi-solid preparations), taila (oil), rasa (mineral preparation), vati (pills), ghrita (fat soluble preparations), churna (powder), dhuma (fumigating preparation), asava (alcoholic preparation) etc.